Bulky granulomatous disease resulting in constrictive tuberculous pericarditis requiring pericardiectomy: a case report. Issue 5 (27th September 2020) - Barua, Sumita; Phua, Bernadette; Orr, Yishay; Skinner, Michael
Abstract: Background : We present a 23-year-old Nepalese migrant with mycobacterial tuberculosis (TB) pericarditis manifesting as effusive constrictive disease and subsequent rapid progression to constrictive pericarditis resulting from bulky granulomatous disease. Case summary : Following initial presumptive diagnosis of TB pericarditis based on presence of moderate pericardial effusion and positive polymerase chain reaction on concurrent pleural aspirate, the patient was managed with standard empiric therapy. Despite treatment, he developed progressive heart failure with New York Heart Association (NYHA) class III symptoms and had confirmation of constrictive physiology on simultaneous left and right heart catheterization. He underwent pericardiectomy 4 months after his initial diagnosis, with debridement of large necrotizing granulomas and an associated immediate improvement clinical improvement. He remains well at 6-month follow-up with no residual heart failure symptoms off diuretic therapy. Discussion : Tuberculous pericarditis accounts for 1–2% of presentations with TB infection, with progression to constrictive pericarditis in between 17 and 40% of cases. To date, pericardiectomy remains mainstay of treatment for constriction, albeit with high perioperative risk. In combination with anti-tuberculous therapy, prednisone and pericardiocentesis may reduce risk of progression to constriction, however, neither have shown mortality benefit. Our patient continued to progress, despite medical therapy and proceeded to pericardiectomy only 4 months after his initial diagnosis, with rapid improvement in symptoms, demonstrating the importance of close monitoring and revision of management strategy in these patients.